Effects of poor communication in the construction industry in Klang Valley, Malaysia - Loh, Brenda Tze Quan; Nur Ilya Farhana Md Noh,; Ng, Jing Lin; Zakiah Ahmad,; Lee, Jin Chai; Salihah Surol,; Deprizon Syamsunur,; Ramez Al-Ezzi Abduljalil Al-Mansob,; Ruzaimah Razman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The construction industry is a risky and complex industry involving various parties characterized with different objectives, skills, cultures, and values. This requires effective communication management to facilitate interaction between them and ensure delivery of successful projects. The poor performance of the Malaysian construction sector has its root in poor communication. Poor communication may result in project failure. Therefore, this paper is essential to investigate the effects of communication issues in the construction industry. This research study was conducted and analysed using SPSS Software. The five-point Likert type scale has been adopted for the questions which is distributed to over 121 respondents who are working in the construction industry around Petaling Jaya, Klang Valley, Malaysia. A total of 8 effects of poor communication in the construction industry were identified. The most dominant effect is time overrun while other effects include project failure, cost overrun, fatal and non-fatal accidents, waste generation, increase carbon footprint and contribute to greenhouse effect. However, questionnaire surveys may result in dishonest answers. Hence, the study recommends conducting physical interviews to better understand respondents view on the negative impacts of poor communication and at the same time, raise awareness as a strategic approach to achieve successful construction projects.